Detailed transcriptome description of the neglected cestode Taenia multiceps. - Xuhang Wu; Yan Fu; Deying Yang; Runhui Zhang; Wanpeng Zheng; Huaming Nie; Yue Xie; Ning Yan; Guiying Hao; Xiaobin Gu; Shuxian Wang; Xuerong Peng; et al. (PLoS ONE, 2012)
BACKGROUND: The larval stage of Taenia multiceps, a global cestode, encysts in the central nervous system (CNS) of sheep and other livestock. This frequently leads to their death and huge socioeconomic losses, especially in developing countries. This parasite can also cause zoonotic infections in humans, but has been largely neglected due to a lack of diagnostic techniques and studies. Recent developments in next-generation sequencing provide an opportunity to explore the transcriptome of T. multiceps. METHODOLOGY/PRINCIPAL FINDINGS: We obtained a total of 31,282 unigenes (mean length 920 bp) using Illumina paired-end sequencing technology and a new Trinity de novo assembler without a referenced genome. Individual transcription molecules were determined by sequence-based annotations and/or domain-based annotations against public databases (Nr, UniprotKB/Swiss-Prot, COG, KEGG, UniProtKB/TrEMBL, InterPro and Pfam). We identified 26,110 (83.47%) unigenes and inferred 20,896 (66.8%) coding sequences (CDS). Further comparative transcripts analysis with other cestodes (Taenia pisiformis, Taenia solium, Echincoccus granulosus and Echincoccus multilocularis) and intestinal parasites (Trichinella spiralis, Ancylostoma caninum and Ascaris suum) showed that 5,100 common genes were shared among three Taenia tapeworms, 261 conserved genes were detected among five Taeniidae cestodes, and 109 common genes were found in four zoonotic intestinal parasites. Some of the common genes were genes required for parasite survival, involved in parasite-host interactions. In addition, we amplified two full-length CDS of unigenes from the common genes using RT-PCR. CONCLUSIONS/SIGNIFICANCE: This study provides an extensive transcriptome of the adult stage of T. multiceps, and demonstrates that comparative transcriptomic investigations deserve to be further studied. This transcriptome dataset forms a substantial public information platform to achieve a fundamental understanding of the biology of T. multiceps, and helps in the identification of drug targets and parasite-host interaction studies.